Association between sedentary time and kidney function in community‐dwelling elderly Japanese people. Issue 5 (14th June 2016) - Lee, Sungchul; Shimada, Hiroyuki; Lee, Sangyoon; Makizako, Hyuma; Doi, Takehiko; Harada, Kazuhiro; Bae, Seongryu; Harada, Kenji; Hotta, Ryo; Tsutsumimoto, Kota; Yoshida, Daisuke; Nakakubo, Sho; et al.
Abstract : Aim: The aim of the present study was to evaluate the relationship between sedentary time and declines in kidney function among community‐dwelling older adults. Methods: Participants comprised 10 242 community‐dwelling older adults who were participating in the National Center for Geriatrics and Gerontology – Study of Geriatric Syndromes. Sedentary time was determined by asking participants to record the total amount of hours usually spent sitting each day, with values divided into quartiles of 0 to <4 h (reference), 4 to <6 h, 6 to <8 h and ≥8 h of sitting time per day. The estimated glomerular filtration rate was determined according to creatinine levels, and participants were classified into two categories: ≥60.0 or <60 mL/min/1.73 m 2 . Results: After multivariate adjustment, the highest quartiles of sedentary time showed a higher rate of kidney function decline than those in the lowest quartile (odds ratio 1.42, 95% CI 1.02–1.37). In addition, participants with a history of cancer (odds ratio 1.18, 95% CI 1.01–1.39) or hypertension (odds ratio 1.38; 95% CI 1.07–1.60) had significantly increased risks of kidney function decline in the highest sedentary time group, regardless of multivariate control. Furthermore, analyses showed an increased risk of kidney function decline for a history of both cancer and hypertension (odds ratio 2.02, 95% CI 1.08–3.80). Conclusions: A higher level of sedentary time was associated with kidney function decline among community‐dwelling older adults.Geriatr Gerontol Int 2017; 17: 730–736 .